Measuring efficiency in electricity distribution from Stochastic Frontier Analysis (SFA) - Cuentas Anci, Hernán (2010)
The objective of this research is to determine the technical efficiency gains of electricity distribution companies in Peru since the establishment of the regime established by Law 25844 on Electricity Concessions in November 1992, using stochastic frontier analysis (SFA).